Molluscicidal activities of ethanolic extracts of Calotropis procera and Morinda lucida against Lymnaea natalensis - Oyeyemi, Oyetunde T.; Eneh, Chioma G.; Okeke, Ijeoma J. (Acta Biologica Szegediensis, 2022)
Snails control is considered the most effective method in reducing the transmission of fascioliasis. Chemical molluscicides are reported to be toxic and ineffective due to snail resistance, hence, the need for safer and effective molluscicides. The aim of this study was to assess the molluscicidal activities of two medicinal plants against snail host of Fasciola gigantica. The molluscicidal activity of Morinda lucida and Calotropis procera was investigated against Lymnaea natalensis, the intermediate host of F. gigantica. Ethanolic extract of leaves of the tested plants were evaluated for their lethal activity against the embryos within the egg masses and adult L. natalensis. All the two tested plants exerted toxic lethal effect against both the embryos and the adult snails. While M. lucida extract appeared to be more potent at lower concentration on the embryos, the extract of C. procera leaves was significantly more potent than that of M. lucida in adult snails (P<0.05). The LC50 of ethanolic extracts of M. lucida and C. procera was 1.698 mg/ml and 0.500 mg/ml, respectively, at 72 h exposure time of adult L. natalensis. The two tested plants have molluscicidal activities, but these activities could be stage specific at certain concentrations.